"You Soak It up Like a Sponge": Urban African American Teens' Perceptions of the Determinants of Dating Abuse Perpetration and Victimization. (8th January 2020) - Storer, Heather L.; Madkour, Aubrey Spriggs; Kendall, Carl
Abstract: Background: African American (AA) teens endure disproportionately high rates of adolescent dating abuse (ADA). There is a limited understanding of the community‐specific pathways that contribute to AA youth's higher risk. The purpose of this study is to investigate AA youths' perspectives on the antecedents of ADA. Methods: Data were collected from interviews ( n = 38) with AA teens. Thematic content analysis was employed to identify primary themes across the interviews. Analysis involved multiple rounds of iterative coding and the clustering of thematic constructs. Results: Interview participants described individual‐level and intergenerational explanations of ADA. The majority of participants could not identify community‐level factors. Discussion and Implications: Dating abuse perpetration and victimization were positioned as the product of personal deficits and exposure to abuse in individuals' family environments. These findings underscore how structural and systemic determinants of dating abuse have not been translated to youth's meaning‐making processes regarding abuse. Implications for diversifying the public discourse on dating abuse will be discussed, and consciousness‐raising on the influence of upstream determinants of abuse will be presented.